Change in surface properties of tooth under cold atmospheric plasma impact - A. V. Aksyuchits; D. A. Kotov; A. N. Osipov; V. Ch. Nedel (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2020)
The article presents the results of experimental studies of the wetting angle of the tooth surface after treatment in the plasma of a dielectric barrier discharge at atmospheric pressure. Measurements of the dependence of the length of the plasma torch and the temperature of the treatment object on the flow rate of the working gas have been carried out. Argon was used as a working gas. The research revealed the possibility to change the length of the plasma torch in the range from 9 mm to more than 25 mm and showed that the temperature of the treated tooth surface with an increase in flow rate from 40 degrees Celsius falls to 32 degrees Celsius. The distilled water wetting angle was determined by the lying drop method. Depending on the processing time, a decrease in the contact angle of the tooth surface wetting from the initial 77 to 20 degrees was observed. The modes of operation of the plasma generator in tooth surface treatment, which provide the best indicators of its wettability, have been determined.